Modelling and simulations of controlled release fertilizer - Irfan, S.A. (American Institute of Physics Inc., 2016)
The recent advancement in controlled release fertilizer has provided an alternative solution to the conventional urea, controlled release fertilizer has a good plant nutrient uptake they are environment friendly. To have an optimum plant intake of nutrients from controlled release fertilizer it is very essential to understand the release characteristics. A mathematical model is developed to predict the release characteristics from polymer coated granule. Numerical simulations are performed by varying the parameters radius of granule, soil water content and soil porosity to study their effect on fertilizer release. Understanding these parameters helps in the better design and improve the efficiency of controlled release fertilizer. Â© 2016 Author(s).